IS THE MANDAMENT VAN SPOLIE AN APPROPRIATE REMEDY IN CASES OF STATUTORY CONFLICTS? Ngqukumba v Minister of Safety and Security 2014 (5) SA 112 (CC) - Lefa S Ntsoane (Obiter, 2017)
The availability of the mandament van spolie in cases where a statutory provision provides for despoilment has been dealt with in a recent Constitutional Court judgment, handed down on 15 May 2014 (Ngqukumba v Minister of Safety and Security 2014 (5) SA 112 (CC)). In this case the Court had to decide on the question whether the mandament van spolie, as a common-law remedy aimed to restore lost possession, can be granted by the Court despite the fact that section 68(6)(b) of the National Road Traffic Act 93 of 1996 prohibits possession “without lawful cause” of a motor vehicle of which the engine or chassis number has been falsified or mutilated. The question was answered in the affirmative. The Court held that the mandament van spolie can be granted, despite the prohibition against the return of the vehicle as provided for by the Traffic Act. This is also the case despite the fact that section 31(1)(a) of the Criminal Procedure Act 51 of 1977 provides for almost the same relief as that which can be achieved by the mandament van spolie, except that the remedy provides for an urgent relief, and it is more cost-effective than resorting to the CPA. In terms of a mandament van spolie, a person who has been unlawfully despoiled of possession may apply to the Court for this remedy, claiming restoration of that possession. The main purpose of the remedy is to protect lost possession of the property by the applicant. This remedy is only concerned with whether the applicant was in factual possession (ius possessionis) of the property, whether movable or immovable, rather than the right to possess (ius possidendi). The merits of the case are therefore not considered by the Court in an application for a mandament van spolie. The aim is to prevent people from taking the law into their own hands by prohibiting the taking of possession otherwise than in accordance with the law . There are two requirements that must first be met for a successful reliance on the mandament van spolie. Firstly, the applicant must prove on a balance of probabilities that he was in peaceful and undisturbed possession of the item. Secondly, the applicant must also prove that the respondent deprived him of possession unlawfully. The first requirement will not be discussed because it was not an issue in this case. A brief analysis of the second requirement will be conducted because of the role it played in this judgment. It is, however, important to mention that these requirements were not the subject of dispute in the present case. This note carries the view that the Ngqukumba judgment strengthened the applicability of the mandament van spolie in cases of dispossession where compliance with due legal process has been compromised. The judgment is important because it promotes the rule of law and due legal process, by ensuring that no one (including organs of State) is above the law. This is particularly true, taking into account the high volume of civil claims lodged by individuals against the Minister of Police in cases where police officials failed to comply with the law. The rule of law has both a procedural and a substantive component. The procedural component of the rule of law requires every action (be it by an individual or an organ of State) to be in accordance with the relevant provisions regulating that act. This is meant to prevent the abuse of power by individuals or Government institutions. The substantive component is concerned with the protection of rights, and this includes the right to dignity, privacy and property. The purpose of this note is threefold. Firstly, the facts, arguments and the judgment will be stated briefly. Secondly, this note will analyse the applicability of the remedy in cases where a statutory provision provides for despoilment. Thirdly, suggestions for a way forward for the applicability of the remedy in cases of a conflict with a statutory provision will be given.